Postoperative Complications among Major Abdominal Surgeries using Clavien-Dindo Classification in Tertiary Hospital: An Observational Study - Manoj Kumar Jha; Kunda Bikram Shah; Anup Thapa; Sunil Basukala; Sumit Kumar Sah (Journal of Nepal Medical Association)
Introduction: The Clavien-Dindo Classification is an easy way to grade any deviation from the post-operative course that is not a normal part of the procedure and does not indicate a failure to achieve the desired cure, regardless of the physician’s age or level of competence. We aimed to conduct a this study to determine the prevalence of post-operative complications after major abdominal surgery and to grade them using the Clavien-Dindo Classification. Methods: This was an observational cross-section study conducted after approval from the Institutional Review Committee (Reference Number: 656). A retrospective data of patients admitted to surgical wards for major surgery from January to June 2022 was included in the study. The post-operative complications were divided as per Clavien-Dindo classification from grade I to grade V. Descriptive statistics was used to analyse data. Results: Out of 78 patients, 45 (57.69%; 95% CI: 52.69%-62.69%) patients had complication after major abdominal surgery. Among them, 17 (37.78%) patients belonged to age group more than 60 years and 24 (53.33%) patients were female. Amongst the morbidities, diabetes mellitus was seen in 7 (15.56%) patients, hypertension in 6 (13.33%), chronic obstructive pulmonary disease in 5 (11.11%) cases and anaemia in 3 (6.67%) cases. There were 19 (42.22%) patient with Clavien-Dindo Classification Grade II and surgical site infection was observed in 26 (57.78%) cases. Conclusions: The prevalence of post-operative complication after major abdominal surgery in our study was found to be comparatively higher as compared to similar studies done in similar settings.